Socioeconomic factors associated with willingness to enroll in orthopedic telemedicine among an underserved urban minority cohort - Eric H. Tischler; Shivasuryan Vummidi; Jake R. McDermott; Ishaq Ibrahim; Elizabeth P. Helzner; Carl B. Paulino (Discover Public Health)
Abstract This prospective survey study aims to assess the sociodemographic factors associated with participation in telemedicine among urban, low-income, racial minority orthopaedic patients presenting to the University Hospital outpatient office. Factors included age, sex, race, education, insurance, travel distance/transportation modality, travel dependence, orthopedic clinic subspecialty, and previous telehealth use. Chart review identified surgical history, ZIP code, and clinic specialty. A total of 521 patients completed the survey, of whom 364 (69.86%) respondents had complete electronic medical record data. Of note, 21.8% (80/364), 20.4% (75/364), and 12.8% (47/364) of patients were Foot and Ankle, Sports, and Spine patients, respectively. Mean cohort age was 46.3 (IQR: 32.8–62.0) with 85.2% (310/364) and 67.9% (247/364) were Black and female, respectively. Although 60.5% (222/364) of patients did not believe telemedicine could resolve their current complaint, 59.4% (218/364) were interested in future telemedicine appointments. Multivariable logistic regression demonstrated education less than high school (OR = 0.38; 95% CI = 0.21–0.68), point-of-service insurance (OR = 0.038, 95% CI = 0.0015–0.39), and spine surgery visits (OR = 0.10, 95% CI = 0.036–0.28) had significantly decreased odds of future orthopaedic telemedicine enrollment. Contrastingly, pediatric patients (OR = 13.55, 95% CI = 2.19–141.25), independent travelers (OR = 2.61, 95% CI = 1.30–5.38), patients who attended appointments from home (OR = 4.34, 95% CI = 1.62–13.14), and patients with positive telemedicine perception (OR = 2.59, 95% CI = 1.54–4.46) had significantly greater odds of future telemedicine enrollment. Telemedicine remains an accessible platform for orthopaedic care, yet willingness to participate among urban socioeconomically disadvantaged orthopaedic patients varies on subspecialty, education, insurance, location, and travel dependence. Orthopaedic telemedicine must consider these factors to ensure equitable access to care.